Kinetika Reaksi Hidrolisis Pati Biji Alpukat (Persea americana Mill) dengan Katalis HCl - Sitti Rahmawati; Asnila Asnila; Suherman Suherman; Paulus Hengky Abram (JIPI (Jurnal IPA dan Pembelajaran IPA), 2020)
One of the plants that can be used as raw material for making sugar is plants that contain starch content such as avocado seeds. This study aims to determine the reaction order, the reaction rate constant from the hydrolysis of avocado seed starch using HCl. The method of this research is to determine the optimum concentration of HCl hydrolysis reaction from avocado seed starch using various concentrations of HCl (0.5 M; 1 M; 1.5 M; 2 M; 2.5 M) at the optimum temperature and stirring time (90oC for 70 minute). The hydrolysis process was followed by neutralization using 5 M NaOH solution and evaporated to obtain concentrated glucose, glucose was analyzed qualitatively and quantitatively by the Benedict method and the phenol sulfuric acid method. Based on the results of the maximum glucose levels obtained from the hydrolysis of variations in the concentration of HCl avocado seed starch, HCl 1.5 M. Furthermore, determine the kinetics of the starch hydrolysis reaction using time variations (30, 40, 50, 60 and 70) minutes at 90oC and concentrations The HCl 1.5 M. reaction order is determined by the intral method and the graph method. Determination of the first order graph method is done by plotting the value of ln [A] versus time, while the second order by plotting the value of 1 / [A] versus time. The first order with a 93% confidence level was obtained from the value of R2 = 0.9312, while the second order was 85% obtained from the value of R2 = 0.8581. Determination of the order of the integral method k value tends to remain in the first order formula with an average of k = 0.01962 minutes-1. Based on the two methods, it can be determined that the kinetics of the avocado seed starch hydrolysis reaction follows a first-order reaction.